3D bioprinting of an electroactive and self‐healing polysaccharide hydrogels. (15th November 2021) - Wang, Yu‐Long; Han, Lu; Zhang, Xin‐Lin; Cao, Long; Hu, Kun; Li, Lu‐Hai; Wei, Yen
Abstract: Polysaccharide hydrogels including alginate, agarose, hyaluronic acid, and chitosan have been widely used as scaffolds in 3D bio‐printing field. Konjac glucomannan (KGM) exhibits excellent properties of water solubility, biocompatibility, and biodegradability. Herein composite hydrogels were prepared via Schiff‐base reaction between the aldehyde group of oxidized konjac glucomannan (OKGM) and the amino group of branched polyethyleneimine (PEI). The OKGM/PEI composite hydrogel displayed self‐healing ability and pH sensitivity and showed shear thinning capability, which is suitable for 3D bio‐printing technology. Furthermore, the OKGM/PEI electroactive composite hydrogel was obtained by adding carbon nanotubes (CNTs). Then the rheological behavior and morphology of OKGM/PEI electroactive hydrogels were thoroughly characterized. The conductivities of OKGM/PEI electroactive composite hydrogels increased with increasing the content of CNTs. The rheological behavior and 3D bio‐printability of OKGM/PEI electroactive hydrogels were also tested. It was found that CNTs can also improve the bio‐printability of OKGM/PEI electroactive hydrogels. Thus, the OKGM/PEI electroactive hydrogels could be employed as scaffolds for muscle and cardiac nerve tissue regeneration.